2010
DOI: 10.1002/chem.200902902
|View full text |Cite
|
Sign up to set email alerts
|

Homoleptic Tris(Pyridyl Pyrazolate) IrIII Complexes: En Route to Highly Efficient Phosphorescent OLEDs

Abstract: Treatment of the metal reagent IrCl(3)nH(2)O with two equivalents of 2-pyridyl pyrazole (N;N)H (3-tert-butyl-5-(2-pyridyl) pyrazole, (bppz)H and 3-trifluoromethyl-5-(2-pyridyl) pyrazole, (fppz)H), afforded the isomeric Ir(III) metal complexes with a general formula cis-[Ir(bppz)(2)Cl(2)]H (2 a), trans-[Ir(bppz)(2)Cl(2)]H (3 a), cis-[Ir(fppz)(2)Cl(2)]H (2 b), and trans-[Ir(fppz)(2)Cl(2)]H (3 b). Single-crystal X-ray diffraction studies on 2 b and 3 a revealed the coexistence of two pyrazolate chelates and two t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(10 citation statements)
references
References 87 publications
(56 reference statements)
1
9
0
Order By: Relevance
“…This is in sharp contrast to the trisbidentate analogue mer-[Ir(fppz) 3 ] that showed the meridional geometry and poor emission efficiency observed at room temperature (RT). 30,31 This photophysical character of mer-[Ir(fppz) 3 ] is also in agreement with the structure−photo- physical behaviors of fac-and mer-[Ir(46dfppy) 3 ], 46dfppyH = 4,6-difluorophenylpyridine, for which the fac-derivative is known to exhibit better photoluminescence at RT versus the mer isomer. 32 We expected that the destabilized metal d π orbitals within the fac isomer might relax, in part, the radiationless deactivation and hence afford better emission efficiency than that of mer counterpart.…”
Section: ■ Introductionsupporting
confidence: 79%
“…This is in sharp contrast to the trisbidentate analogue mer-[Ir(fppz) 3 ] that showed the meridional geometry and poor emission efficiency observed at room temperature (RT). 30,31 This photophysical character of mer-[Ir(fppz) 3 ] is also in agreement with the structure−photo- physical behaviors of fac-and mer-[Ir(46dfppy) 3 ], 46dfppyH = 4,6-difluorophenylpyridine, for which the fac-derivative is known to exhibit better photoluminescence at RT versus the mer isomer. 32 We expected that the destabilized metal d π orbitals within the fac isomer might relax, in part, the radiationless deactivation and hence afford better emission efficiency than that of mer counterpart.…”
Section: ■ Introductionsupporting
confidence: 79%
“…The accompanied long tailing band, signifying the dual emission, possesses the inherent MLCT character that is mixed slimly with respect to ligand-centered ππ* transition. This takes place once the energy gap between the lower-lying MLCT and ligand-centered ππ* states are small and thermally accessible as well as the two states are distinct in electronic configuration and hence the corresponding structures . In order to analyze the two-state relation between MLCT and ππ* states, a series of time-resolved emission spectra were acquired across 380–600 nm (Figure S5).…”
Section: Resultsmentioning
confidence: 99%
“…This takes place once the energy gap between the lower-lying MLCT and ligandcentered ππ* states are small and thermally accessible as well as the two states are distinct in electronic configuration and hence the corresponding structures. 45 In order to analyze the two-state relation between MLCT and ππ* states, a series of time-resolved emission spectra were acquired across 380−600 nm (Figure S5). The results led us to propose a mechanism depicted in Figure S6, where there exist two close lying triplet states, the LE (ππ*) and CT (MLCT) states, both of which possess slightly different geometry and are populated by the fast rate of adiabatic crossing (beyond our instrument response time of 100 ps).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Chen et al. reported a series of homoleptic tris(pyridyl pyrazolate) Ir(III) complexes ( 108 – 113 ) 86. The OLED study of 112 (which had the highest quantum efficiency amongst those reported) as the dopant showed a maximum external quantum efficiency as high as 14.6 %.…”
Section: Conjugated Metallo‐organic Small Molecules For Oled Applimentioning
confidence: 99%